Two Different Perspectives about How to Specify and Implement Multiagent Systems - Rosa, André Mendes da; Gularte, Alexander; Gonçalves, Eder Mateus Nunes; Jung, Mateus (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
This article review has as a goal to demonstrate that exists two different perspectives considering the actual literature about frameworks to specify and implement multi-agent systems in a formal way. On the one hand, there are those specific frameworks/methodologies for MAS where those obligatory requirements to guarantee the system correctness are encapsulated on the tool. On the other hand, there are those frameworks/methodologies that are based on those existing one and they are adapted to the multi-agent specificities, where those mechanisms to verify and validate the system are inherited from the original method/tool. On this paper are presented two methodologies based on the first perspective, considering three different dimensions on specifying MAS, and two adapted tool, Petri Nets and AUML, considering the second perspective.